2021
DOI: 10.1007/s10826-021-02070-7
|View full text |Cite
|
Sign up to set email alerts
|

Combining Motherhood and Work: Effects of Dual Identity and Identity Conflict on Well-Being

Abstract: This study investigated whether having a dual identity as both a mother and an employed person constitutes a threat to well-being, or whether it is a positive resource. The study focused on indices of life satisfaction and self-esteem. A convenience sample of 208 mothers were exposed to a manipulation of identity conflict, whereby we manipulated whether working mothers perceived their identities as a mother and an employed person to be in conflict with each other or not. It was hypothesized that generally havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…, 2012; Millward, 2006). The purpose of job crafting for working mothers is not only to improve work-related outcomes but also to enhance the overall effectiveness in the family domain (Zagefka et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2012; Millward, 2006). The purpose of job crafting for working mothers is not only to improve work-related outcomes but also to enhance the overall effectiveness in the family domain (Zagefka et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that women who focus in a working mother role identity are likely to have a more positive attitude and transfer it to their family domain. A study conducted on a sample of 208 working mothers found a positive association between a woman with a working mother role identity and wellbeing (Zagefka et al, 2021). In sum, job crafting tactics improve work-to-family enrichment through an engagement in role identity.…”
Section: Mothers' Job Craftingmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the shadow prices of her health and well-being increase, suggesting a decrease in her health and well-being (Chatterji and Markowitz 2005). However, if labor market work enhances maternal (mental) health as well (Grzywacz and Bass 2003;Brook et al 2008;Zagefka et al 2021), there might be a "cut-off" length of leave that still yields positive effects. Thus, as health and wellbeing improve with time and market goods, the effect of paid parental leave on health and wellbeing is unclear.…”
Section: Maternal Time Allocation and Well-being Of Mother And Childmentioning
confidence: 99%
“…Disorders in the mother-infant relationship concern 10 to 25% of mothers referred to a psychiatrist (Brockington 1996). However, if no role conflicts exist and new mothers adapt, this fosters well-being by boosting identification sources and self-esteem (Grzywacz and Bass 2003;Brook et al 2008;Zagefka et al 2021).…”
Section: Maternal Time Allocation and Well-being Of Mother And Childmentioning
confidence: 99%